Implementation of a Quality Management System in Micro, Small, and Medium Enterprises in Solok Regency - Aflidarneti Aflidarneti; Fadillah Tri Sari Nasrul; Lusiana Lusiana (LaKaspia, 2026)
This study aims to describe the implementation of an ISO 9000-based quality management system in Micro, Small, and Medium Enterprises (MSMEs) in Solok Regency by integrating modern management perspectives and Islamic business ethics. The ISO 9000 standard, developed by the International Organization for Standardization, emphasizes customer focus, a process approach, continuous improvement, and evidence-based decision-making. These principles are conceptually aligned with Islamic values such as itqan (professional excellence and precision), trustworthiness (amanah), and accountability in economic activities, as discussed by Yusuf al-Qaradawi and Al-Ghazali. This research employs a descriptive qualitative approach, using in-depth interviews, observations, and document analysis as data collection techniques. Data were analyzed through systematic stages of reduction, presentation, and conclusion drawing. The findings indicate that MSMEs have substantively applied quality principles through their commitment to maintaining product quality and customer satisfaction. However, the implementation remains informal, lacking structured documentation and standardized written operating procedures. The integration of ISO 9000 principles and Islamic ethical values has the potential to strengthen systematic and sustainable quality governance, ensuring that quality improvement is institutionalized within a structured management system rather than relying solely on moral commitment.